KETERTARIKAN MASYARAKAT PEGADUNGAN TERHADAP PENDALAMAN BAKAT BIDANG SENI SEBAGAI AKTIVITAS SEPULANG SEKOLAH - Joshua Christian Chandra; Nina Carina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Pegadungan area, West Jakarta is a housing settlement. As a residential area, this area has several educational facilities (schools). But to be able to grow and develop, other facilities are needed such as the development of talent in certain fields that can be visited after school hours. Thus the activities of children after school can be contained positively. At this time the deepening of talent and skills in an academic and non-academic field is one of the important factors in children's development. Besides, Pegadungan Village also has people who are professionals as traders and employees. Where most of the offices in Jakarta are located in the center of the city that has very heavy traffic, the people who work as employees also need a place to take a break from the office world. Through questionnaire methods and theories from the book "The Rise of the Creative Class, Revisited" by Richard Florida, it is known that Pegadungan Village needs a place for refreshing and deepening talent in the arts as well as the development of SMEs. So that with the Project Architecture as The Third place with Development of Interest Activity is expected to be a container that produces creative products from people in Pegadungan Village. Keywords: After school Activity; After School life; Creative; Development of interest; RefreshingAbstrakKelurahan Pegadungan adalah kelurahan dengan zonasi perumahan. Sebagai suatu kawasan perumahan, kelurahan ini memiliki fasilitas pendidikan (sekolah) yang cukup banyak. Namun untuk dapat bertumbuh dan berkembang, diperlukan fasilitas lain seperti pendalaman bakat pada bidang tertentu yang dapat di kunjungi seusai jam sekolah agar aktivitas anak di luar jam sekolah dapat terwadahi dengan positif. Pada saat ini pendalaman bakat dan ketrampilan pada suatu bidang baik dalam akademis maupun non-akademis menjadi salah satu faktor penting dalam perkembangan anak. Selain itu, Sebagian penduduk merupakan orang-orang dengan profesi sebagai pedagang juga karyawan yang membutuhkan tempat untuk rehat sejenak dari dunia perkantoran. Melalui metode kuisioner dan teori dari buku “The Rise Of The Creative Class, Revisited” by Richard Florida diketahui bahwa Kelurahan Pegadungan membutuhkan tempat untuk refreshing dan pendalaman bakat pada bidang kesenian juga pengembangan UKM. Sehingga dengan adanya Project Third Place Architecture dengan mengangkat aktivitas pendalaman bakat pada suatu bidang diharapkan dapat menjadi wadah yang menghasilkan produk-produk kreatif dari penduduk di Kelurahan Pegadungan.